2018
DOI: 10.1002/ar.23780
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide AF Induces Piecemeal Degranulation in Murine Mucosal Mast Cells: A New Mediator in Neuro‐Immune Communication in the Intestinal Lamina Propria?

Abstract: Neuropeptides AF (NPAF), FF (NPFF) and SF (NPSF) are RFamide neuropeptides known to be widely expressed in the mammalian central nervous system, where they fulfill a wide range of functions with pain modulation being the most prominent one. Recent evidence indicates that RFamides act as mediators in mast cell–sensory nerve communications related to allergic disease. Previous work by our group has shown that the expression levels of some members of the Mas‐related gene receptor (Mrgpr) family in both enteric ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, Mrgprc11 is activated by neuropeptide AF (NPAF) and neuropeptide FF (NPFF), two FMRF‐amide peptides with a role in pain signaling . It was recently found that their common precursor gene is expressed by myenteric neurons and mucosal‐type mast cells, acting as a possible source for these ligands . Moreover, a growing body of evidence links Mrgprc11 to protease‐mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mrgprc11 is activated by neuropeptide AF (NPAF) and neuropeptide FF (NPFF), two FMRF‐amide peptides with a role in pain signaling . It was recently found that their common precursor gene is expressed by myenteric neurons and mucosal‐type mast cells, acting as a possible source for these ligands . Moreover, a growing body of evidence links Mrgprc11 to protease‐mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 It was recently found that their common precursor gene is expressed by myenteric neurons and mucosal-type mast cells, acting as a possible source for these ligands. 39 Moreover, a growing body of evidence links Mrgprc11 to protease-mediated signaling. Established protease-activated receptor 2 (PAR-2) agonists, such as the PAR-2 tethered-ligand peptide SLIGRL and certain cysteine proteases, also act as Mrgprc11 agonists, thereby inducing effects that were previously considered to be solely PAR2-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that Mrgprb10 was expressed de novo in mucosal MCs of Schistosoma mansoni ‐infected ileum (Avula et al, 2013) and that in vitro mucosal‐type bone marrow‐derived mast cells (BMDMCs) were found to express Mrgpra1 and Mrgpra4 mRNA, but these findings have not been confirmed in vivo (Abdellah et al, 2018). Plum et al (2020) demonstrated MRGPRX2 expression in human gut MCs.…”
Section: Mrgpr Expression In the Gastrointestinal Tractmentioning
confidence: 99%
“…Furthermore, MrgprC11 is known to be activated by two FMRF‐amide peptides, neuropeptide AF (NPAF) and neuropeptide FF (NPFF), which have been reported to act as mediators in MC‐sensory nerve communications (Lee et al, 2008; Lee et al, 2011; Tatemoto et al, 2006). We were able to identify, by means of RT‐PCR, possible RF‐amide sources in intrinsic and extrinsic components of the ENS, that is, in DRGs and in enteric neurons and intestinal MCs (Abdellah et al, 2018). Furthermore, immunofluorescent staining with a FMRFamide antibody clearly revealed the presence of FMRFamide in nerve fibers in both the myenteric and submucous plexuses as well as in neuroendocrine cells with typical neuropods.…”
Section: Mrgprs: Novel Targets In Chronic Abdominal Pain Disorders?mentioning
confidence: 99%
See 1 more Smart Citation